DOUBLE-STAGE SAVONIUS AND DARRIEUS WIND TURBINES FOR URBAN AREAS USING FIBERGLASS MATERIALS - Wijayanto, Danar Susilo; Soenarto, Soenarto; Triyono, Mochammad Bruri; Ibadi, Husni (Journal of Applied Engineering Science, 2022)
Wind generation is an alternative to energy generation that is renewable, widely distributed, and environmentally friendly. However, the use of wind energy in certain areas with limited land has constraints for installing large-scale generators; therefore, the concept of micro wind energy generation is an attractive solution to be developed at this time. In this case, the Vertical Axis Wind Turbine (VAWT) is preferred because it is reliable and economically feasible to operate at low wind speeds in all wind directions. In the case of turbine selection, the Savonius turbine is preferred because it has self-starting. Still, in terms of performance, the Darrieus turbine type has better power efficiency than the Savonius type. Besides that, because of their high solidity and heavier weight, drag-based turbines are less preferred. In this study, the combination of the two types of turbines between Savonius and Darrieus was carried out to overcome each type of turbine’s shortcomings. In this case, the fiberglass material was chosen because it has reliable properties that increase the turbine’s efficiency. The research design used an experimental method by configuring a double-stage Savonius-Darrieus turbine in the wind tunnel. The data was collected by measuring and recording the electric voltage, electric current, and the generator shaft rotation for each variation of the pitch angle at the 0°,5°,10°,15°,20°,25° and 30° blades and with wind speeds at 1.5 m/s up to 5 m/s with 0.1 m/s intervals. The results showed that adding variations in the pitch angle of the Savonius-Darrieus double-stage turbine blade was ineffective because it reduced the electric power generated and the turbine’s performance. In this study, the resulting cut-in speed is 3.8 m/s. However, with the addition of variations in the pitch angle, there was a decrease in the value of electric power, power coefficient, and Tip Speed Ratio (TSR), where the maximum values were 3.14 W, 0.24, and 0.75, respectively.